The Effect Of Giving Natural ZPT On The Growth Of Cocoa Stem Cuttings (Theobroma cacao L.) From Plagiotropic Clonal Cocoa (PCC) Sulawesi Clone - Fadhil Rachman Mutaqien; Nisa Budi Arifiana; Triono Bambang Irawan (Politeknik Pertanian Negeri Samarinda, 2025)
Cocoa (Theobrama cacao L.) is one of the plantation products that has a very high economic value. Cocoa productivity has decreased every year. In 2019, cocoa productivity in Indonesia was 734,795 thousand tons and has decreased every year until 2022, cocoa productivity was 650,612 thousand tons. To overcome this, plant rejuvenation and provision of superior planting materials are needed. One common propagation technique is stem cuttings, which is growing new plants from parts of the parent plant. The success of propagation through cuttings is highly dependent on the ability of the cuttings to grow roots, a process that can be enhanced by administering plant growth regulators, especially those from the auxin group. This study aims to evaluate the effect of natural plant growth regulator (PGR) concentrations on clonal stem cuttings of Plagiotropic Cocoa (PCC) Sulawesi 01. The experiment was conducted from August 2024 to January 2025 at the Jember State Polytechnic. The non-factorial Randomized Complete Block Design (RBD) used was P0 (control), P1 to P4 (long bean sprout extract concentrations of 20%, 40%, 60%, and 80%, respectively), and P5 to P8 (coconut water concentrations of 20%, 40%, 60%, and 80%, respectively). Each treatment was repeated three times, with two experimental samples per replication. The results showed that the administration of natural ZPT at the highest coconut water concentration (80%, P8) significantly increased shoot height at 90, 120, and 150 days after planting (DAP), as well as root length at 150 DAP, compared to other treatments.